Latin American modern architectures : ambiguous territories - Del Real, Patricio, 1966-; Gyger, Helen (New York : Routledge, 2013)
"Latin American Modern Architectures has thirteen new essays from a range of distinguished architectural historians to help you understand the region's rich and varied architecture. It will also introduce you to major projects that haven't been written about in English. A foreword by historian Kenneth Frampton sets the stage for essays on well-known architects, such as Luis Barragán and Félix Candela, which will show you unfamiliar aspects of their work, and for essays on the work of little-known architects, such as Lucio Costa and Joaquim Cardozo, which will spark your creativity. This book is your best source for historical and critical essays on a sampling of Latin America's diverse architecture, providing much-needed information on key case studies"--
pt. I. Singular journeys -- pt. II. Techno-cultural assemblages -- pt. III. Mediated territories.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Architecture -- Latin America -- History -- 20th century; Electronic books